Intrahousehold preference heterogeneity and demand for labor-saving agricultural technology - Gulati, Kajal; Ward, Patrick S.; Lybbert, Travis J.; Spielman, David J. (Wiley, 2024)
Evaluations of agricultural technologies rarely consider the implications of how adoption may alter the labor allocation of different individuals within a household. We examine intrahousehold decision-making dynamics that shape smallholder households' decision to use mechanical rice transplanting (MRT), a technology that disproportionately influences demand for women's labor. To study the adoption decision, we experimentally estimate the willingness to pay for MRT services both at the individual and household level. We find that women value MRT more than men, especially when they participate in transplanting on their own farms. This preference heterogeneity is evident in the unconditional differences between women's and men's valuation and differences conditional on their individual observable characteristics. Despite having stronger preferences for MRT, women have less influence on the household's technology adoption decision than men. This differential influence over the MRT adoption decision reflects the intrahousehold power structure: in households where women have less control over assets, they also have less influence over the MRT adoption decision. Our results highlight how technological changes interact with unobserved, gender-based intrahousehold power relations to influence agricultural production decisions and, by extension, the gendered allocation of labor and welfare of women.